2020
DOI: 10.3390/ijerph17020628
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness and Device-Measured Sedentary Behaviour are Associated with Sickness Absence in Office Workers

Abstract: Physical activity reduces the risk of several noncommunicable diseases, and a number of studies have found self-reported physical activity to be associated with sickness absence. The aim of this study was to examine if cardiorespiratory fitness, device-measured physical activity, and sedentary behaviour were associated with sickness absence among office workers. Participants were recruited from two Swedish companies. Data on sickness absence (frequency and duration) and covariates were collected via questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Previous studies described low CRF among various groups of office workers [ 8 , 10 ]. The importance of CRF for office workers was also shown in a study by Drake et al [ 49 ], which presented significantly lower frequencies and durations of absence due to sickness among office workers with higher CRF.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies described low CRF among various groups of office workers [ 8 , 10 ]. The importance of CRF for office workers was also shown in a study by Drake et al [ 49 ], which presented significantly lower frequencies and durations of absence due to sickness among office workers with higher CRF.…”
Section: Discussionsupporting
confidence: 57%
“…The present results are consistent with those from prior studies pointing out the beneficial influence of cardiorespiratory fitness on sickness absence. Drake et al found among office workers that high cardiorespiratory fitness decreased risk for all-cause sickness absence [ 8 ], while similar results found in nursing personnel with recurrent nonspecific low back pain [ 9 ]. However, while a positive influence of cardiorespiratory fitness was evident in our study, accelerometer-measured physical activity levels and meeting the physical activity recommendations did not show a statistically significant relationship with the number of sickness absence days, self-perceived work ability or quality of life.…”
Section: Discussionmentioning
confidence: 90%
“…Consequently, physical activity may hold the potential to decrease the amount of sickness absence [ 6 ], which today constitutes an economically significant burden on employers and society at large [ 7 ]. Moreover, high cardiorespiratory fitness could play an especially significant role in reducing the duration and frequency of these absences [ 8 ]. Finally, there may be a link also between high cardiorespiratory and muscular fitness, coupled with engaging in the recommended amount of physical activity (at least 150 minutes of moderate- or 75 minutes of vigorous-intensity physical activity each week) [ 5 ], and lower total healthcare costs, at least among nursing personnel with recurrent low-back pain [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the association between sedentary behaviors and the type of work (o ce work, manual work, work in a care setting...) is clearly demonstrated, with o ce workers spending 66% of their waking time in a seated position, compared to 59% for all workers, and barely 47% for manual workers (34). The health of workers is thus impaired with more cases of obesity, absenteeism, and depression and anxiety among the most sedentary workers (24,(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%